Modeling farmers’ willingness to engage in traceability systems: toward sustainable agricultural transformation - Huang, Yatao; Fu, Shaoling (Frontiers in Sustainable Food Systems, 2023)
The primary objective of this study is to examine the factors that affect farmers' willingness to engage in traceability systems. Traceability systems are widely promoted as technologies that ensure the quality and safety of agricultural products. However, the participation rate of farmers in developing countries remains low. To empirically address this issue, the study analyzed structured interview data from 408 fruit farmers in Henan Province, Central China, using structural equation modeling and system dynamics. The results indicate that attitude, perceived behavioral control, subjective norms, moral norms, and safety awareness are crucial factors influencing farmers' willingness to engage. It is particularly noteworthy that system dynamics simulations revealed the significant role of improving attitude and subjective norms in promoting farmers' willingness. Moreover, subjective norms have a positive influence on moral norms. We also found that gender, education, orchard area, income and access to credit have a significant positive impact on farmers' willingness to engage. By uncovering the internal decision-making mechanisms behind farmers' engagement in traceability systems, this study extends the research scope of agricultural technology adoption. These findings can serve as a basis for formulating traceability system policies and interventions in China and other developing countries.